2015
DOI: 10.1021/acs.jpcc.5b03863
|View full text |Cite
|
Sign up to set email alerts
|

Surface Chemistry of “Unprotected” Nanoparticles: A Spectroscopic Investigation on Colloidal Particles

Abstract: The preparation of colloidal nanoparticles in alkaline ethylene glycol is a powerful approach for the preparation of model catalysts and ligand-functionalized nanoparticles. For these systems the term "unprotected" nanoparticles has been established because no strongly binding stabilizers are required to achieve stable colloids. Irrespective of this fact, the particles must be considered as being covered by adsorbates, as otherwise the particles would coalesce and precipitate. The identification of these prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

15
134
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 70 publications
(150 citation statements)
references
References 32 publications
15
134
1
Order By: Relevance
“…Most reports stress that the reaction occurs only in strictly alkaline solution, therefore an excess of NaOH is typically used for the syntheses . However, based on recent results we proposed that the use of no or low NaOH concentrations should allow for tuning the size of surfactant‐free NPs . Here we demonstrate that this postulation was correct, but the use of UV light instead of thermal energy is needed as a driving force in order to kinetically inhibit sintering processes.…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…Most reports stress that the reaction occurs only in strictly alkaline solution, therefore an excess of NaOH is typically used for the syntheses . However, based on recent results we proposed that the use of no or low NaOH concentrations should allow for tuning the size of surfactant‐free NPs . Here we demonstrate that this postulation was correct, but the use of UV light instead of thermal energy is needed as a driving force in order to kinetically inhibit sintering processes.…”
Section: Figurementioning
confidence: 99%
“…However, organic compounds that play a role in the reaction mechanism and NP stabilization might be observable using IR. Consistent with previous results by Schrader et al., the negative pointing absorption peaks around 2900 cm −1 can be attributed to ethylene glycol and the peak around 1650 cm −1 relates to water. In addition, the IR data shows a peak around 1600 cm −1 which could be due to C=C containing compounds that are produced as the reaction media becomes more alkaline and Pt NPs are present.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…360 nm). c) Detailed investigation of different absorption bands that appeared by the end of formation of Pt NPs after ≈2000 h. Red curve: PtNPs suspension; pink curve: Pt NPs re‐dispersed in EG; brown curve: supernatant of Pt NP suspension; green curve: difference between red and pink curves (the peak shift most likely is related to a shift in OH − concentration during the re‐dispersion procedure) …”
Section: Figurementioning
confidence: 99%
“…EDS (see Supporting Information) confirmed that the observed NPs are indeed Pt. Comparing daylight‐induced NP formation at RT to our standard heat‐induced Pt NP synthesis (see Figure d), the former results in an average particle size that is slightly larger and exhibits a somewhat broader size distribution as a consequence of different precursor concentrations and slower reaction kinetics (see discussion of particle growth in the Supporting Information). In previous work, UV‐light‐induced Pt NP formation has been reported in combination with strongly binding ligands, which limit catalytic applications .…”
Section: Figurementioning
confidence: 99%